(untitled) (Purbanchal University Health Journal, 2022)
Introduction: Rapidly growing elderly population is witnessing poor health status and decreasing functional capacity affecting overall health of the individuals globally. In Nepal awareness level about special needs of elderly and elderly care (Physical, psychological and social needs) is very low which directly affect the Quality Of Life (QOL) of elderly. Objective: The objective of the study was to assess the quality of life among elderly people residing in Dhodegaun, Nepalgunj. Method: It was a cross sectional study conducted at Dhodegaun, Nepalgunj from October 2018 to July 2019 among 100 elderly people. The samples were chosen through consecutive sampling. A standardized and validated WHO Quality of Life- BREF (WHOQOL-BREF) questionnaire was used. Permission for study was taken from Bheri Nursing College, Nepalgunj. Informed consent from each participant was taken. Confidentiality and privacy of participants was maintained in the study. Result: Majority of respondents (83%) had a fair QOL whereas; none of them had excellent QOL. The QOL score of elderly was found better in the environmental domain (83.36 ±12.34) whereas; social domain was worse (35.36 ± 6.88). The physical and psychological domains of QOL in male were significantly better as compared to females. The physical, psychological and social domains of QOL in married elderly (60-70 years) with absence of disease were significantly better as compared to the age group more than 70 years who were widow/er and had illness. Whereas only the psychological and environmental domain of QOL in elderly people with primary level education was significantly better as compared to illiterate elderly people. Conclusion: The QOL score was highest in the environmental domain while it was lowest in the social domain. This emphasizes that community people and policy makers should focus on the need for more social support-related interventions among elderly in the community.